The modern concept of special economic zones in Ukraine - Liashenko Viacheslav; Pidorycheva Iryna; Mytsenko Ivan; Chebotarova Nataliia (Bulletin of Geography. Socio-Economic Series, 2021)
The article deals with special economic zones as a tool of state policy of countries seeking to attract foreign investment and ensure economic growth. The aim of the article is to substantiate the new concept of special economic zones of Ukraine as stimulating regulatory regimes aimed at attracting innovative investments and developing new industries based on the smart specialisation of regions and trends in the world economy. The regime is presented as a system of incentives and benefits, mandatory conditions and restrictions, and seeks to increase the investment attractiveness and technological diversification of the economy of the regions and the country as a whole. Each component of the regime has been classified, taking into account best practices of other countries and the strategic goals of Ukraine regarding the need to ensure sustainable and innovative development and to enter the world markets as a manufacturer of high-tech innovative products.